Improving the stability of titania nanosheets by functionalization with polyelectrolytes. Issue 99 (11th October 2016) - Rouster, Paul; Pavlovic, Marko; Szilagyi, Istvan
Abstract : Highly stable suspensions of titanate nanosheets were designed by surface functionalization with P(AAm- co -DADMAC) copolymer. Abstract : Titania nanosheets (TNS) have been synthesized by the hydrothermal method and functionalized with poly(diallyldimethylammonium chloride) (PDADMAC) or poly(acrylamide- co -diallyldimethylammonium chloride) (P(AAm- co -DADMAC)) polyelectrolytes. The morphology and the composition of the materials were investigated by X-ray diffraction and microscopy techniques. The polyelectrolyte coating led to dramatic changes in the charging behavior and in the colloidal stability of the TNS in aqueous suspensions, as revealed by electrophoretic and light scattering measurements. The adsorption of PDADMAC and P(AAm- co -DADMAC) on the oppositely charged TNS surface gave rise to charge neutralization and charge reversal at appropriate polyelectrolyte doses and to unstable and stable suspensions, respectively. In the latter situation, the polyelectrolyte functionalized nanosheets were resistant against aggregation even at high ionic strengths where the bare TNS rapidly aggregated. Highly stable suspensions were obtained especially in the presence of P(AAm- co -DADMAC) layer on the TNS surface due to the repulsive interparticle forces originating from both electrostatic and steric interactions. The obtained suspensions of excellent colloidal stability are promising candidates as carrier systems for instance in biomedical treatments, where homogeneous distribution of primary particles is required for the delivery of biologically active molecules.